Sevoflurane exposure induces neurotoxicity by regulating mitochondrial function of microglia due to NAD insufficiency - Zhu, Ruilou; Zeng, Shuang; Li, Ningning; Fu, Ningning; Wang, Yangyang; Miao, Mengrong; Yang, Yitian; Sun, Mingyang; Zhang, Jiaqiang (Frontiers in Cellular Neuroscience, 2022)
Developmental neurons received with sevoflurane, the commonly used inhalational anesthetic agent in clinical surgery, several times tend to be destroyed. Microglia, the resident immune cells of the central nervous system (CNS), are activated after sevoflurane exposure, accompanied by releasing proinflammatory cytokines that damage developing neurons. The sevoflurane-induced neurotoxicity could be attributed to activated microglia presenting proinflammatory and anti-inflammatory functions. Proinflammatory microglia release cytokines to impair the CNS, while anti-inflammatory microglia engulf damaged neurons to maintain CNS homeostasis. Sevoflurane exposure promotes the secretion of proinflammatory cytokines by microglia, inhibiting the microglial phagocytic function. Microglia with poor phagocytic function cannot engulf damaged neurons, leading to the accumulation of damaged neurons. The mechanism underlying poor phagocytic function may be attributed to mitochondrial dysfunction of microglia induced by sevoflurane exposure, in which affected mitochondria cannot generate adequate ATP and NAD to satisfy the energy demand. We discovered that sevoflurane treatment impaired the mitochondrial metabolism of microglia, which resulted in NAD deficiency and couldn’t produce sufficient energy to clear damaged neurons to maintain CNS development. Our findings provide an explanation of a new mechanism underlying sevoflurane-induced neurotoxicity.